BRAND AWARENESS, BRAND CREDIBILITY, BRAND SELF-CONGRUITY AND PURCHASE INTENTION FOR LUXURY BRANDS (I.E. HANDBAG): AN EMPIRICAL STUDY OF CHINESE CONSUMERS - Hanpu Chen; Salmi Mohd Isa; Shaohua Yang (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The aim of this paper is to examine the determinants of Chinese consumers’ purchase intention for luxury brands (i.e. handbag) by testing a theoretical model. Quantitative method was adopted to confirm each hypothesis. A random sample of 231 Chinese consumers who have purchased luxury handbags was invited to complete survey form. The findings of this study revealed that brand awareness, brand credibility and brand self-congruity have a direct impact on Chinese consumers’ purchase intention for luxury handbags. The results of this study are beneficial not only to marketing scholars for understanding a theoretical model on the Chinese consumers’ purchase behaviour in luxury handbags but also to luxury brand (i.e. handbag) retailers for offering suggestions which help them develop marketing strategies to achieve more revenues.